Mental health services for Syrian refugees in Europe. Critical review - Nujiedat , Zaied (Kultura-Społeczeństwo-Edukacja, 2020)
The purpose of this paper is to present background information about Syrian refugee mental health who arrived at Europe Union countries between 2015-2018 and provide statistics about prevalence to some mental health related issues. As well as illustrating the challenges and barrier to provide effective Syrian refugee mental health services. In addition, this paper presents some European countries experience in intervention program to improve mental health among Syrian refugee with providing examples about German and Jordan. This paper provided examples about some wide used programs in EU and middle East Countries that used to deal with refugee mental health issues such as STRENGTH program, PM+ and MHGAP. Many recommendations were suggested with focus on providing culture and language sensitive psychotherapy for refugee in EU countries.